'Assessment and care management'--a hospital perspective. - Taylor, I. C. (Ulster Medical Society, 1994)
Patients placed from hospital to nursing or residential homes or to home under the intensive domiciliary care scheme were compared before and after the introduction of 'assessment and care management' on the 1st April 1993. In geriatric medical wards there was a 69% increase in the average length of stay for patients assessed and care managed and a 52% increase in the length of stay for self-funding patients compared with patients placed before the introduction of assessment and care management. Care managed patients discharged on the intensive domiciliary care scheme had a 66% increase in their length of hospital stay compared with care managed patients placed in private nursing homes. In contrast, the length of stay for care managed patients in other hospital wards was half that for geriatric medical wards.